STRATEGI PROMOSI PERKREDITAN PADA PT BPR INTIDANA - Endang Suparni; Aris Kurniawan (Institut Teknologi dan Bisnis Dewantara, 2020)
Promotion is one of the strategies in the marketing mix in a company, where its function is to introduce and promote products or services to prospective customers or consumers. The purpose of this study was to determine the promotion strategy carried out by PT. BPR Intidana. The type of research is descriptive qualitative which is collecting and processing data and analysis of promotion strategies implemented by PT. BPR Intidana. The technique in collecting data uses interviews and observations, by asking questions directly, the object under study is in accordance with the research. The data source comes from secondary data from various kinds of literature, company documents and so on. In promoting its products, PT.BPR Intidana uses all promotional mixes, namely: advertising through print media, personal selling through marketing personnel, sales promotion by giving gifts, and publicity by sponsoring an activity. Promotion strategies carried out by PT. BPR Intidana is expected to increase the number of customers provided by the credit facility and provide a positive image in the eyes of the public.